Effects of Essential Oils from 24 Plant Species on Sitophilus zeamais Motsch (Coleoptera, Curculionidae) - William R. Patiño-Bayona; Leidy J. Nagles Galeano; Jenifer J. Bustos Cortes; Wilman A. Delgado Ávila; Eddy Herrera Daza; Luis E. Cuca Suárez; Juliet A. Prieto-Rodríguez; Oscar J. Patiño-Ladino (Insects, 2021)
Chemical control of the maize weevil (Sitophilus zeamais) has been ineffective and presents serious collateral damage. Among plant-derived insecticides, essential oils (EOs) are suitable candidates to control this stored products pest. In this work, the insecticidal activities of 45 natural EOs against S. zeamais adults were screened, and the most promising ones (24 EOs) were characterized by GC–MS. The repellent and toxic effects (contact and fumigant) of these 24 EOs were determined, and by a cluster analysis they were classified into two groups considering its fumigant activity and contact toxicity. For the EOs with the highest fumigant potential (14 oils) and their main active constituents (17 compounds), lethal concentrations were determined. The most active EOs were those obtained from L. stoechas and L. alba, with LC50 values of 303.4 and 254.1 µL/L air and characterized by a high content of monoterpenes. Regarding the major compounds, the oxygenated monoterpenes R-(+)-pulegone (LC50 = 0.580 mg/L air), S-(-)-pulegone (LC50 = 0.971 mg/L air) and R-(-)-carvone (LC50 = 1.423 mg/L air) were the most active, as few variations in their concentrations significantly increased insect mortality.